Dalbavancin as suppressive antibiotic therapy in patients with prosthetic infections: efficacy and safety - Ruiz-Sancho, Andrés; Núñez-Núñez, María; Castelo-Corral, Laura; Martínez-Marcos, Francisco Javier; Lois-Martínez, Nagore; Abdul-Aziz, Mohd Hafiz; Vinuesa-García, David (Frontiers in Pharmacology, 2023)
Suppressive antibiotic therapy (SAT) is a strategy to alleviate symptoms and/or to reduce the progression of an infection when other treatment options cannot be used. Dalbavancin due to its prolonged half-life enables (bi)weekly dosing. Here, we report our multicenter real-life clinical experience with dalbavancin used as SAT in patients with prosthetic joint or vascular infections. Medical records of all adult patients with documented vascular or orthopedic chronic prosthetic infections, who received dalbavancin as SAT between 2016 and 2018 from four Spanish hospitals were reviewed for inclusion. Descriptive analysis of demographic characteristics, Charlson Comorbidity index, Barthel index, isolated pathogens and indication, concomitant antibiotic use, adverse events and clinical outcome of SAT were performed. Eight patients were eligible for inclusion where 6 patients had prosthetic vascular infections (aortic valve) and two patients had knee prosthetic joint infections. Most common pathogens were methicillin-susceptible Staphylococcus aureus and Enterococcus faecium. All patients had a history of prior antibiotic treatment for the prosthetic infection (median duration of antibiotic days 125 days [IQR, 28-203 days]). Median number of dalbavancin doses was 29 (IQR, 9-61) and concomitant antibiotic use (n=5, 62.5%). Clinical success was reported in 75% (n=6) of patients. Adverse events were reported in 2 patients (mild renal and hepatic impairment). Despite the limitations of our study, this preliminary data provides valuable insight to support further evaluation of dalbavancin for SAT in patients with prosthetic infections in the outpatient setting when alternative treatments are not feasible.